PENGARUH K3 BERBASIS PROTOKOL KESEHATAN, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA DESA PRAMANA SWAN - Kurniawati, Ni Putu Ayu Tika; Paramananda, N.; Artha Aryasa, I Putu Gde Chandra (Akses: Jurnal Penelitian dan Pengabdian Kepada Masyarakat Universitas Ngurah Rai, 2022)
This study aims to determine the effect of K3 based on health protocols, organizational culture and work environment on employee productivity at Desa Pramana Swan. This study uses all employees from Pramana Swan Village as a sample, which is 145 employees with saturated sampling technique. Methods of collecting data using interviews and questionnaires. Data analysis used descriptive analysis, multiple linear regression analysis, and the coefficient of determination test. The results showed that K3 based on health protocols, organizational culture and work environment partially had a positive and significant effect on employee work productivity at Desa Pramana Swan. The researcher concludes that if the health protocol-based K3 is implemented properly, the organizational culture and work environment are also good, the work productivity of employees at Desa Pramana Swan will increase. The suggestion from this research is to be able to optimize K3 based on health protocols by providing health support facilities. Organizational culture is best done by creating a positive atmosphere both as individuals and in teams so that employees feel able to work well to achieve more optimal goals, while the quality of the work environment provided to employees should be improved so that company goals can be achieved.